2019
DOI: 10.1007/s12325-019-00964-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Developing Additional Immune-Mediated Manifestations: A Retrospective Matched Cohort Study

Abstract: IntroductionImmune-mediated inflammatory diseases (IMIDs) cause significant impairment in quality of life. Although they share similar genetic factors, environmental precipitants, and pathophysiological mechanisms, there is little evidence on the risk of developing subsequent IMIDs after an initial IMID diagnosis. We sought to assess the risk of developing subsequent IMIDs among patients diagnosed with an initial IMID.MethodsThis retrospective matched cohort study used a large US commercial health insurance cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 18 publications
0
55
0
6
Order By: Relevance
“…On the one hand, the limited number of patients, and on the other, its retrospective nature with the lack of follow-up of some patients. Furthermore, some studies have shown an association between HS and Crohn's disease [24], as well as with other IMIDs such as rheumatoid arthritis, psoriatic arthritis, and ankylosing spondylitis [25]. It has been hypothesized that IMIDs share common genetic origins that may increase patients' susceptibility to the development of multiple, apparently unrelated IMIDs.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the limited number of patients, and on the other, its retrospective nature with the lack of follow-up of some patients. Furthermore, some studies have shown an association between HS and Crohn's disease [24], as well as with other IMIDs such as rheumatoid arthritis, psoriatic arthritis, and ankylosing spondylitis [25]. It has been hypothesized that IMIDs share common genetic origins that may increase patients' susceptibility to the development of multiple, apparently unrelated IMIDs.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of these studies are outlined in Tables 1 and 2. The studies were published between 2007 and 2019 and conducted in the USA [10,11,13,17,18], Korea [9,14,15], Denmark [12,16], and Finland [19]. Three publications [15][16][17] were retrospective cohort studies, two [18,19] were case-control studies and the other six [9][10][11][12][13][14] were cross-sectional studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The studies were published between 2007 and 2019 and conducted in the USA [10,11,13,17,18], Korea [9,14,15], Denmark [12,16], and Finland [19]. Three publications [15][16][17] were retrospective cohort studies, two [18,19] were case-control studies and the other six [9][10][11][12][13][14] were cross-sectional studies. Six studies [9,12,[14][15][16] were based on nationwide populationbased databases, four [10,11,13,17] were based on large administrative databases and the other one [18] was based on single-center biobank.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search identified 3 risk factors associated with IBD: concomitant hidradenitis suppurativa (HS) [37][38][39][40][41] (supplementary Fig. S5 and Table S4), presence of the first-degree relative with IBD 42-57 (supplementary Fig.…”
Section: Impact Of Risk Factors On Ibd In Patients Exposed To Il-17imentioning
confidence: 99%